Analysis of Motor Vehicle Tax (PKB) Payment Service Quality through Mobile Samsat Service : Case Study at the Joint Samsat Office of Surabaya - Achmat Firman Alfaris; Kristyan Dwijosusilo; Dandy Wirawan; Kresna Adhi Prahmana (International Journal of Sociology and Law, 2026)
Quality public services are central to improving taxpayer compliance and optimizing Regional Original Revenue (PAD). The Mobile Samsat service at the Joint Samsat Office (Kantor Bersama Samsat) Surabaya represents a significant innovation designed to facilitate access to Motor Vehicle Tax (PKB) payments, particularly for residents living far from the main Samsat office. This study aims to analyze the quality of PKB payment services through the Mobile Samsat in Surabaya using a descriptive qualitative approach, applying Parasuraman's (1988) SERVQUAL theory, which encompasses five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected through in-depth interviews, direct observation, and documentation. The results indicate that service quality is generally satisfactory across most dimensions. Tangibles remain a concern as some Mobile Samsat locations lack adequate waiting facilities and are positioned in crowded roadside areas. Reliability is strong, with services consistently delivered according to schedule and standard operating procedures. Responsiveness is excellent, as officers process payments in an average of 2–5 minutes. Assurance is well-established through officer competence, transparency of service costs, and professional demeanor. Empathy is evident in the personalized attention provided by officers to taxpayers of all backgrounds. Therefore, the Joint Samsat Office of Surabaya is recommended to improve physical facilities at service locations, broaden the dissemination of service schedules and routes through multiple media channels, and evaluate operational locations to enhance taxpayer comfort and overall service quality.